Chylous Ascites due to Mantle Cell Lymphoma - Ricardo Jorge Gonçalves Fernandes; Márcia Leite; Joana Cochicho; Rafaela Veríssimo; Agripino Oliveira (European Journal of Case Reports in Internal Medicine, 2018)
Chylous ascites is rare and results in accumulation of lymph in the abdominal cavity, due to several mechanisms. The ascitic liquid is milky because of the high concentration of triglycerides (>200 mg/dl). The higher incidence compared to the past is explained by increased survival of patients with cancer and more aggressive surgery. We describe the case of an 87-year-old man admitted to the geriatric ward due to general oedema, chylous ascites and loss of weight, explained by mantle cell lymphoma.